Eksistensi Perempuan Dalam Novel Re Dan Perempuan Karya Maman Suherman - Ridwan, Ridwan; Rapi, Muhammad; Lisma, Lisma (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2024)
This research aims to find out how the existence of women in the novel Re and Perempuan by Maman using the feminism theory approach. This research is qualitative descriptive. The data in this study comes from quotations in the novel related to women's existence. reading and note-taking techniques are applied in the data collection process. The reading technique is used to understand and interpret the content of the text, while the note-taking technique focuses on the female characters in the novel who experience various types of oppression and injustice. The results of this study are as follows: first, the presence of female characters. The female characters in this novel are women who eventually succeed and achieve the freedom they dream of, but are trapped in situations that limit them. Secondly, the life of women in society, prostitutes who are considered as the scum of society even though their existence is the result of the existing economic inequality. Third, women in education show that the social level of parents cannot be a benchmark for children's education. Melur, who was born from a prostitute, was able to get a PhD. The theory used in this research is Simmone de Beaouvier's existentialist feminism theory. Existentialist feminism examines how the existence of female characters in living their lives.